Quaternion model of enhanced rotating polarization wave for robust higher order modulation Low Power Wide Area Network wireless communication - Ahmad, Zaid (2022)
The growing interest in Industry 4.0 has spurred the demand for reliable wireless communication. Low-Power Wide-Area Networks (LPWANs) have pivotal role in emerging applications such as Internet of Things (IoT) and Machine-to-machine (M2M) communication wherein massive number of sparsely located machines and sensor nodes are connected. Reliability and robustness are compromised when LPWANs are deployed to support industrial grade communication. Moreover, critical IoT applications have pressing demands for high data rate and extended coverage with minimal information loss. The design requirements of wireless M2M systems influence the choice of modulation and diversity techniques, and the selection of spectrum. Rotating Polarization Wave (RPW) is an LPWAN technology tested for highly reliable M2M communication. It is a hybrid polarization-based modulation that exploits Binary Phase Shift Keying (BPSK) and Polarization Diversity (PD) to provide robust wireless connectivity. In this thesis, an enhanced RPW modulation is proposed whereby a novel pair of complementary Multilevel PSK (MPSK) modulators successfully generates an RPW waveform with multiple phase shifts, hence termed as Rotating Polarization Multilevel Phase-Shift Keying (RPMPSK). A novel channel model is also proposed that exploits quaternions to account for the impact of multipath fading and channel depolarization on RPW transmission. The model is referred to as Quaternion RPW (Q-RPW) model in this thesis. Q-RPW simplifies computation involved in modeling and simulation of RPW that is otherwise complex if classical dual-polarized channel models are employed. Performance of RP-MPSK over multipath fading channel under noise and interference conditions has been evaluated in terms of Bit Error Rate BER using the proposed Q-RPW model. The results show that uncoded RP-MPSK modulation with the smallest sampling ratio of 3 attains BER profile similar to that of BPSK system with second-order space diversity. Further improvement in BER performance can be achieved provided higher sampling ratios are maintained. Therefore, sampling ratio on RP-MPSK receiver is a practical tradeoff between reliability and data rate. RPW with RP-MPSK also outperforms all other forms of polarization in terms of BER. A comprehensive link budget analysis is performed to demonstrate the potential of RPW as an enabling technology for LPWAN. Sensitivity, Received Signal Strength (RSS), and maximum range of RPW is determined. Results show that RP-MPSK exhibits an excellent sensitivity level of -114 dBm under multipath conditions. The minimum RSS in urban settings is -85 dBm while the maximum range achieved by RP-MPSK in rural areas is 15 km despite shadowing and multipath fading. RPW with proposed RP-MPSK modulation offers transmission rate of up to 500 kbps with a channel bandwidth of 125 kHz. However, in ISM band, channel bandwidth can be increased to 500 kHz. Consequently, potential transmission rates of up to 2 Mbps are feasible. Higher data rates translate to increased energy efficiency as more data is transmitted in shorter time intervals to counterpoise duty cycle limitations of ISM band.